PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA KATERING SHOBIA DI KELURAHAN SUNGAI MALANG KECAMATAN AMUNTAI TENGAH - Hasanah, Nurul; Fatmawati, Fatmawati (PPPM STIA Amuntai, 2023)
Increasingly advanced technology and increasing activity at the present time make people prefer practical ways of fulfilling food and drinks for themselves, as well as for certain events. Plus the fast growing catering business in Indonesia, one of which is the catering business. Catering is always related to consumers, where customer satisfaction is one of the most important things for the continuity of catering. Consumer satisfaction is influenced by several factors, one of which is the quality of existing products. This study aims to determine the effect of product quality on customer satisfaction at Shobia Catering in Sungai Malang Village, Central Amuntai District. The research method used is a quantitative research method. The population of this research is some consumers who buy products at Shobia Catering. Samples taken as many as 100 samples. While the data was collected using a questionnaire or questionnaire as the main method and dokumentation as a complementary method. Data analysis techniques used instrument tests (validity and reliability tests), simple linear regression analysis, T-test, and the coefficient of determination (R2) using the SPSS Version 22 application. The results showed that there was a significant influence between product quality variables on customer satisfaction at Shobia Catering. Because the results of the hypothesis can be seen that tcount (7.838) > ttable (1.664) and a significant value (0.000) < (0.05). In addition, it can also be seen that the Cronbach's Alpha value on the product quality variable is 0.638 > 0.60 and the Cronbach's Alpha value on the consumer satisfaction variable is 0.853 > 0.60 so it can be concluded that the two variables are declared reliable. The R2-test the product quality factor has an influence of 38.5% on consumer satisfaction, while the remaining 61.5% is influenced by other variables not included in this study